Effects of Sea Spray on Microphysics and Intensity of Deep Convective Clouds Under Strong Winds. Issue 16 (20th August 2019) - Shpund, J.; Khain, A.; Rosenfeld, D.
Abstract: Deep convective clouds similar to those arising in the tropical cyclone eyewall are simulated using a parcel model and 2‐D slab symmetric cloud model with spectral bin microphysics (the Hebrew University Cloud Model). The size distribution of sea spray particles (SSPs) at cloud base is calculated using the Lagrangian‐Eulerian bin microphysics model. The model describes the SSP production, advection, and formation of the size distribution of SSP in the hurricane atmospheric boundary layer at different strong wind speeds. The SSP distributions calculated by the Lagrangian‐Eulerian bin microphysics model are used in the parcel model and the Hebrew University Cloud Model to investigate the microphysical and dynamical effects of SSP on clouds. The SSPs ascending in cloud updrafts dramatically increase the number concentration of cloud drops within a wide range of drop sizes. As a result, sea spray creates clouds with unique property combinations of both maritime and continental types. These clouds have droplet size distributions characterized by a high drop concentration and a low effective radius, as in continental clouds. At the same time, the presence of SSP of a few hundred microns in radii triggers intense rain just above the cloud base, which is typical of extreme maritime clouds. In the presence of large sea spray drops, the smallest cloud condensational nuclei, including the smallest SSP, are activated, giving rise to the permanent in‐cloud nucleation of small droplets, which produce a high concentration of small ice crystals above the level of homogeneous freezing. We showed that the SSP substantially increased the maximum vertical velocity, cloud water content, and mass contents of ice particles. The results are compared with available observed data. Key Points: Deep convective clouds typical of eyewall of TCs are simulated Sea spray particles, production, and transport at strong winds are simulated using Eulerian‐Lagrangian model and are transported to clouds Sea spray particles produce a new type of clouds having both continental and maritime properties; SSPs lead to convection invigoration